1987
DOI: 10.1111/j.1469-185x.1987.tb01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Character Diagnosis, Fossils and the Origin of Tetrapods

Abstract: SUMMARY I. The traditional view of the origin of tetrapod vertebrates is that they are descendants of fossil osteolepiform fish, of which Eusthenopteron is best known. In recent years both that conclusion and the methodology by which it has been reached have been challenged by practitioners of cladistic analysis. Particularly a recent review by Rosen et al. (1981) claims that Dipnoi (lungfish) are the sister‐group of the Tetrapoda, that Osteolepiformes is a non‐taxon and that Eusthenopteron is more distant fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
147
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 95 publications
8
147
1
Order By: Relevance
“…One essential adaptation in the evolution of tetrapods was the ability to locomote on land, a trait that required significant morphological and functional changes in the appendicular system. Many of these morphological changes can be observed in the fossil record (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Work on basal tetrapod fossils has revealed that even those with digited limbs can be aquatic (5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One essential adaptation in the evolution of tetrapods was the ability to locomote on land, a trait that required significant morphological and functional changes in the appendicular system. Many of these morphological changes can be observed in the fossil record (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Work on basal tetrapod fossils has revealed that even those with digited limbs can be aquatic (5,7).…”
mentioning
confidence: 99%
“…Lungfishes, including P. annectens, are the sister group to living tetrapods (2,4,15), and as such are important for understanding the evolution of movement patterns and limb function in this group. P. annectens is clearly specialized relative to other sarcopterygians in that its fins are longer and more slender than all other known examples (16,17).…”
mentioning
confidence: 99%
“…However, now they are reduced to only three relict genera that are found in Australia, Africa, and South America (Neoceratodus, Protopterus, and Lepidosiren;Forey 1987;Cloutier and Forey 1991). Despite much research there is still no general agreement regarding the phylogenetic relationships among Actinistia, Dipnoi, and Rhipidistia (including Tetrapoda; Ahlberg 1991; Cloutier and Ahlberg 1996;Forey 1988Long 1995;Maisey 1996;Marshall and Schultze 1992;Meyer 1995;Nelson 1994;Panchen and Smithson 1987;Rosen et al 1981;Schultze 1994). This controversy will continue until new relevant fossils of intermediate forms connecting the three groups are discovered, and agreement among paleontologists about the homology of some characters (e.g., the choanae) is achieved (Forey 1988;Schultze 1994;Rosen et al 1981).…”
mentioning
confidence: 99%
“…Panchen and Smithson 1987). This major evolutionary transition involved many sweeping morphological (e.g., evolution of limbs and air breathing), physiological, and behavioral changes, but nonetheless it seems to have taken place within an astonishingly short period of time of only 10-20 million years (Carroll 1988;Maisey 1996;Cloutier and Ahlberg 1996).…”
mentioning
confidence: 99%
“…Previously, Panchen and Smithson (1987) discussed many of the points made here. (1) Cladistic methodology is necessary for a solution to this problem.…”
Section: Toward a Resolution Of The Origin Of Tetrapodsmentioning
confidence: 99%